2022
DOI: 10.3390/plants11202738
|View full text |Cite
|
Sign up to set email alerts
|

Application of Rhizobacteria, Paraburkholderia fungorum and Delftia sp. Confer Cadmium Tolerance in Rapeseed (Brassica campestris) through Modulating Antioxidant Defense and Glyoxalase Systems

Abstract: We investigated the role of two different plant growth-promoting probiotic bacteria in conferring cadmium (Cd) tolerance in rapeseed (Brassica campestris cv. BARI Sarisha-14) through improving reactive oxygen species scavenging, antioxidant defense, and glyoxalase system. Soil, as well as seeds of rapeseed, were separately treated with probiotic bacteria, Paraburkholderia fungorum BRRh-4 and Delftia sp. BTL-M2. Fourteen-day-old seedlings were exposed to 0.25 and 0.5 mM CdCl2 for two weeks. Cadmium-treated plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Among the numerous studies of catalase and peroxidase activity under stressful conditions, conclusions about the activation of these enzymes after the use of growth-stimulating bacteria prevail. Such results were obtained for canola under salinity [ 60 , 61 ], Cd stress [ 62 ], and wheat under Zn stress [ 59 ], drought [ 63 , 64 ], and salinity [ 65 ]. However, our data indicated that the changes in CAT activity were a consequence rather than a cause of the alleviation of herbicidal stress.…”
Section: Discussionmentioning
confidence: 69%
“…Among the numerous studies of catalase and peroxidase activity under stressful conditions, conclusions about the activation of these enzymes after the use of growth-stimulating bacteria prevail. Such results were obtained for canola under salinity [ 60 , 61 ], Cd stress [ 62 ], and wheat under Zn stress [ 59 ], drought [ 63 , 64 ], and salinity [ 65 ]. However, our data indicated that the changes in CAT activity were a consequence rather than a cause of the alleviation of herbicidal stress.…”
Section: Discussionmentioning
confidence: 69%